Influence of lipid content and stirring behaviour on furan and furan derivative exposure in filter coffee. (15th July 2019) - Rahn, Anja; Fankhauser, Nina; Yeretzian, Chahan
Highlights: Lipid content of dairy condiments added to coffee is critical in coffee furan retention. Stirring hot coffee can significantly reduce furan exposure. Condiments added at high temperatures reduce furan exposure. Abstract: Coffee has been determined as the dominant source of furan within an adult's diet. This study investigates the influence of coffee condiment use and stirring on the retention of furan. Three condiment lipid compositions were investigated, 0%, 3.5% and 35%, and kept at either 4 °C, 20 °C or 70 °C before addition to a freshly brewed cup of filter coffee which was subsequently mechanically stirred at three intensities, not stirred and moderately or heavily stirred. While five furans were monitored, furan, 2-methylfuran, 3-methylfuran, 2, 5-dimethylfuran and 2, 3-dimethylfuran, only two were quantifiable: furan and 2-methylfuran. Increasing condiment lipid concentration significantly increased retention of furan and 2-methylfuran, whereas stirring the coffee significantly increased furan release. A condiment temperature of 70 °C was found to significantly increase furan release.